Liquefaction Potential Analysis Based on Nonlinear Ground Response on the Coastline of Bengkulu City, Indonesia - Mase, Lindung Zalbuin (UI Scholars Hub, 2020)
This paper presents the study of the seismic response and liquefaction potential of the coastal area of Bengkulu City during the September 2007 Sumatra earthquake. The study is conducted by collecting site investigation data (standard penetration test) and applying input motion to observe soil response. Synthetic ground motion is generated by considering the important aspects of earthquakes, including focal depth, epicenter, earthquake source, and site classification. The synthetized ground motion is then used as the input motion in the seismic response analysis. The results of this analysis are spectral acceleration and peak ground acceleration at each depth. The resulting spectral acceleration is compared with that specified in the seismic design code of Indonesia (SNI 03-1726-2012). Liquefaction potential analysis is performed on the basis of the results of the seismic response analysis. Results show that spectral acceleration depends on soil type. A high soil density equates to a low spectral response. The designed spectral acceleration may still be considered for each borehole, especially for T (period) < 1. However, for T > 1, spectral acceleration should be prioritized, especially for high-rise building construction. The liquefaction analysis reveals that a shallow depth is vulnerable to liquefaction. In general, this study could give a better understanding on the implementation of seismic ground response for liquefaction potential analysis.